Nonlinear propagation of ultrasound through microbubble clouds: A novel numerical implementation - Hibbs, K; Mari, J; Stride, E; Eckersley, R; Noble, A; Tang, M; IEEE (2007)
Nonlinear propagation of ultrasound can cause imaging errors in the context of medical ultrasound with microbubble ultrasound contrast agents. Modelling nonlinear propagation of ultrasound through a microbubble cloud is therefore essential for simulating the phenomenon to understand the causes of these errors and to develop suitable error correction techniques to reduce these imaging errors. Such models do exist but large discrepancies are found when simulation results are compared to experimental data. In this work the reasons for these inaccuracies are examined and a more realistic approach is proposed. © 2007 IEEE.